2021
DOI: 10.1016/j.msard.2021.103157
|View full text |Cite
|
Sign up to set email alerts
|

T-cell responses to SARS-CoV-2 in multiple sclerosis patients treated with ocrelizumab healed from COVID-19 with absent or low anti-spike antibody titers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 11 publications
3
36
0
1
Order By: Relevance
“…( Bar-Or et al, 2020 ) In OCR-treated patients, several studies have shown an impaired humoral response yet preserved T-cell response following SARS-CoV-2 infection or vaccination with Pfizer-BioNTech COVID-19 (BNT162b2) or Moderna Tx, Inc (mRNA-1273). ( Kister et al, 2021 , Achiron et al, 2021 , Sormani et al, 2021 , Apostolidis et al, 2021 , Iannetta et al, 2021 ) In contrast, natalizumab (NTZ), an α4-integrin monoclonal antibody, is unlikely to impact vaccine efficacy. ( Kaufman et al, 2014 )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Bar-Or et al, 2020 ) In OCR-treated patients, several studies have shown an impaired humoral response yet preserved T-cell response following SARS-CoV-2 infection or vaccination with Pfizer-BioNTech COVID-19 (BNT162b2) or Moderna Tx, Inc (mRNA-1273). ( Kister et al, 2021 , Achiron et al, 2021 , Sormani et al, 2021 , Apostolidis et al, 2021 , Iannetta et al, 2021 ) In contrast, natalizumab (NTZ), an α4-integrin monoclonal antibody, is unlikely to impact vaccine efficacy. ( Kaufman et al, 2014 )…”
Section: Introductionmentioning
confidence: 99%
“…2 In OCR-treated patients, several studies have shown an impaired humoral response yet preserved T-cell response following SARS-CoV-2 infection or vaccination with Pfizer-BioNTech COVID- 19 (BNT162b2) or Moderna Tx, Inc (mRNA-1273). [7][8][9][10][11] In contrast, natalizumab (NTZ), an α4-integrin monoclonal antibody, is unlikely to impact vaccine efficacy. 12 In this study, we evaluated the humoral response to SARS-CoV-2 vaccines in adult MS patients treated with OCR, using NTZ as a real-world comparator.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously investigated SARS-CoV-2 specific T-cell responses in PwMS on ocrelizumab treatment, healed from COVID-19, using an interferon (IFN)-γ release assay (IGRA) after overnight stimulation of whole blood with SARS-CoV-2 specific peptide libraries. Despite the lack of an antibody response to the natural infection, we were able to identify a specific T-cell response in all the healed subjects included in the study ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of SARS-CoV-2 infection and vaccination have already described specific cellular responses in the absence of humoral responses. 12 , 13 , 29 In fact, a study of COVID-19 patients with hematologic cancer treated with rituximab showed that those with a higher proportion of T cells had a better outcome. 30 Therefore, the cellular response might play an important role in COVID-19 recovery when humoral immunity is impaired.…”
Section: Discussionmentioning
confidence: 99%